Neuropsychological Outcome following Resuscitation after Out-of-Hospital Cardiac Arrest: A One-Year Follow-Up - Jeannette Overbeck; Frank-Michael Schweers (Case Reports in Cardiology)
A 61-year-old woman survived resuscitation after out-of-hospital cardiac arrest. The heterogeneity of the resulting cognitive impairments and the recovery over a one-year period are presented, highlighting the need for standardized neuropsychological testing even after short cardiac arrests and for effective treatment both out of hospital and in hospital.